PENGARUH PEMBERIAN TINGKAT KONSENTRASI PUPUK URINE KELINCI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L.) PADA VARIETAS YANG BERBEDA - Kartina AM; Andi Apriany Fatmawaty; Dian Angga Widyanto (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2020)
This research aimed to know the effect of giving urine concentrations of rabbits and different varieties on the growth and yield of maize. The research was conducted on land owned by CV Hardian Cipocok Jaya District Serang City Banten Province from November 2019 until February 2020. The research used a Randomized Completely Block Design with two factors. The first factor was the concentration of rabbit urine fertilizer which consisted of three levels, namely: 20 ppm, 30 ppm, and 40 ppm. The second factor was the variety which consisted of 3 levels, namely indurata, pulut and black aztec. The result showed that rabbit urine fertilizer with a concentration of 30 ppm showed better results on plant height parameters aged 14 days after planting (28.11 cm), 21 days after planting (46.33 cm), 28 days after planting (71.22 cm), 35 days after planting ( 103.24 cm), 42 days after planting (131.87 cm), 49 days after planting (154.37 cm), the number of leaves 14 days after planting (2.89 pieces) and the number of leaves at 21 days after planting (4.22 strands). Indurata variety showed better results on the parameter of the number of leaves aged 14 days after planting (2.67 pieces). There was no interaction between treatment rabbit urine fertilizer at various levels of concentration with various varieties of maize except for plant height parameters aged 14 days after planting and 21 days after planting and the number of leaves aged 14 days after planting and 21 days after planting.